PENERAPAN METODE BERNYANYI DALAM PEMBELAJARAN BAHASA DAN MATEMATIKA DI TKIT AR-RAHMAN - Nova Perlita; Novi Andri; Dwi Sumiwi; Afiffudin (Jejaring Penelitian dan Pengabdian Masyarakat, 2023)
Learning is a series of events designed in such a way as to influence and support the learning process of students. Learning must certainly be designed to be an interesting learning and in great demand by students. To realize this, a learning method that is in accordance with the target of students is needed, especially for children. They need special educational units especially in their knowledge of language and mathematics to meet the needs of their growth and development. Children usually have more fun when singing because it can make them more excited and more motivated.Â Therefore, it is necessary to conduct research using classroom actions to prove that this singing method is very effective for learning in children. Research using class actions certainly has several stages including planning, implementation and assessment. After an assessment of the effectiveness of this singing method, it is proven that this method can make children become more motivated and have a strong memory. Not only that, children also become more active in the learning process.